Structured programming concepts - LaBudde, Keith P. (New York : McGraw Hill Education, 1987)
This book is intended fo use in an introduction to business programming course. This course may be the first data processing course a student takes; it may be taken along with an introductory course as a prerequisite.
1. the Programming Process -- 2. Introduction to Structured Programming -- 3. Conditions That Control Processing -- 4. Complex Combinations of Conditions -- 5. Control Breaks -- 6. Multilevel Control Breaks -- 7. Tables -- 8. Multifile Processing: Sequential Access -- 9. Multifile Processing: Direct Access.
Includes index.
Keywords: ELECTRONIC DIGITAL COMPUTERS -- PROGRAMMING